Moving forward with backward pedaling: a review on eccentric cycling - Barreto, Renan Vieira [UNESP]; Lima, Leonardo Coelho Rabello de [UNESP]; Denadai, Benedito Sergio [UNESP] (Springer, 2020)
Purpose There is a profound gap in the understanding of the eccentric cycling intensity continuum, which prevents accurate exercise prescription based on desired physiological responses. This may underestimate the applicability of eccentric cycling for different training purposes. Thus, we aimed to summarize recent research findings and screen for possible new approaches in the prescription and investigation of eccentric cycling. Method A search for the most relevant and state-of-the-art literature on eccentric cycling was conducted on the PubMed database. Literature from reference lists was also included when relevant. Results Transversal studies present comparisons between physiological responses to eccentric and concentric cycling, performed at the same absolute power output or metabolic load. Longitudinal studies evaluate responses to eccentric cycling training by comparing them with concentric cycling and resistance training outcomes. Only one study investigated maximal eccentric cycling capacity and there are no investigations on physiological thresholds and/or exercise intensity domains during eccentric cycling. No study investigated different protocols of eccentric cycling training and the chronic effects of different load configurations. Conclusion Describing physiological responses to eccentric cycling based on its maximal exercise capacity may be a better way to understand it. The available evidence indicates that clinical populations may benefit from improvements in aerobic power/capacity, exercise tolerance, strength and muscle mass, while healthy and trained individuals may require different eccentric cycling training approaches to benefit from similar improvements. There is limited evidence regarding the mechanisms of acute physiological and chronic adaptive responses to eccentric cycling.
Keywords: Aerobic capacity; Exercise domains; Fatigue; Aerobic training; Exercise tolerance; Strength training